A Japanese case of successful surgical resection of cerebral cavernous malformations with a CCM2 mutation. Issue 5 (29th June 2022) - Nomura, Emi; Omote, Yoshio; Takemoto, Mami; Hishikawa, Nozomi; Nakano, Yumiko; Yunoki, Taijun; Morihara, Ryuta; Sasaki, Tatsuya; Akagawa, Hiroyuki; Abe, Koji; Yamashita, Toru
Abstract: Cerebral cavernous malformations (CCMs) are congenital abnormalities of cerebral vessels. Surgical resection is rarely considered for the control of epilepsy in a first seizure patient with vascular malformation. In contrast, lesions that produce repetitive or progressive symptoms should be considered for surgical resection as treatment. Herein, we report a Japanese patient with a CCM2 mutation, c.609G>A (p.K203K) substitution, who showed drug‐resistant epilepsy and dramatic improvement after surgical resection.